ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH PADA BPK-AD KANTOR WALIKOTA MANADO - Thebora, Patras; Morasa, Jenny; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The  objective  of  this  research  is  to  examine  the  factors  that  influence  information  value  of  local  government  financial  reporting.  Information  value  refers  to  reliability  and  timeliness.  The  factors  that  influence  reliability  and  timeliness are human resource quality, information technology utilization,internal control system, and local financial monitoring.Local government financial management must be done according to the good governance, that are transparent and accountable, that allow users of financial statement to acces about theresult that local government accomplish. The objective of this research is to investigate the impact of human resources quality, utilization of information technology, local government financial controlling, and internal control system toward value of financial report information, which is timeliness. The research is talking place in BPK-AD of Mayor’s Office, Manado. The research method used is quantitative, and the sample is all the population of the officer that works for the research object. The hypothesis test conclude that human resources quality, and utilization of information technology do not have significant impact, while local government financial control and internal control system do have significant effect towards timeliness of financial reporting in BPK-AD of Mayor’s Office, Manado.Keyword : Information value, Local Government Financial Report, Human resource quality, utilization of information technologies, local government financial control, and internal control system